2006
DOI: 10.1188/06.onf.593-601
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Sick Leave Benefits, Employment Patterns, and Individual Characteristics to Radiation Therapy-Related Fatigue

Abstract: Management of treatment side effects, including fatigue, may help patients remain in the workforce during radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…Other studies have identiWed that fatigue under RCT is related to unemployment [41] and that chemotherapy as such correlated with higher disability and quitting work [42]. This might explain why acquiring, keeping and terminating a job (d875) is more problematic and labor and employment services (e590) are more relevant to the RCTgroup.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies have identiWed that fatigue under RCT is related to unemployment [41] and that chemotherapy as such correlated with higher disability and quitting work [42]. This might explain why acquiring, keeping and terminating a job (d875) is more problematic and labor and employment services (e590) are more relevant to the RCTgroup.…”
Section: Discussionmentioning
confidence: 97%
“…Fatigue was described as a common problem in the literature (Saligan et al, 2013;Bryant-Lukosius et al, 2010;Maliski et al, 2008), increasing after one week of radiotherapy and peaking significantly at the end of treatment (Saligan et al, 2013;Knapp et al, 2012;McCaughan et al, 2013;Poirier, 2006). However, one month after external radiotherapy no significant difference between patients with non-metastatic prostate cancer undergoing radiotherapy and healthy men was shown (Saligan et al, 2013).…”
Section: Fatiguementioning
confidence: 91%
“…A large body of evidence exists to support the finding that CRF during anti-cancer treatment is not associated with tumour stage (12,22,23,46,51,56,60,(68)(69)(70) or any demographic (12,22,23,34,49,55,56,60,62,64,(66)(67)(68)(69)(70)(71) or treatment-related variables (12,22,23,46,51,53,55,60,64,(68)(69)(70)(71)(72). In contrast, two studies have reported that females experience more fatigue then males (62,73), three have demonstrated an association between increasing age and lower fatigue (12,34,53), one between marital status and fatigue, with divorced women experiencing the most fatigue (74), two between working and raised fatigue …”
Section: Fatigue During Anti-cancer Treatmentmentioning
confidence: 94%
“…In a chemotherapy study of breast and ovarian cancer patients, those with a diagnosis of ovarian cancer experienced worse fatigue (4). It is plausible that fatigue severity increases with advancing stage of the disease (10), however CRF has also been shown to be unrelated to disease stage (12). Fatigue is frequently reported as a common side effect of most chemotherapy regimes; nevertheless there have been some conflicting findings in this area (13).…”
Section: Introductionmentioning
confidence: 93%